impact of interval marketing on market- oriented considering mediatory variables of organizational commitment and organizational citizenship behavior: case of Mellat bank of Tehran. - Tahmoures Hassangholipour; Manouchehr Ansari; Akram Elahigol; Hossein Rahmani Youshanloei (تحقیقات بازار یابی نوین, 2012)
The purpose of this paper is to examine the relationship between "internal marketing" and "market orientation" considering the mediator variable of "organizational commitment" in branches of Bank Mellat in the city of Tehran as a financial-service provider firm. The questionnaire in this study has been extracted from the related literature and its validity has been approved by the field experts and factor analysis. The research methodology adopted in this study is typically descriptive and correlation based and the collected data has been analyzed using Structural Equation Modeling (SEM) approach. Research population consisted of Bank Mellat employees throughout the city of Tehran. A sample of 323 employees has been selected using cluster sampling and finally, 261 filled questionnaires has been collected. Findings imply that there is a positive correlation between internal marketing and market orientation considering the mediator variable of organizational commitment in the Bank Mellat of the city of Tehran.